Estimation of the long term helium production in high burn-up spent fuel due to alpha decay and consequences for the canister. Issue 1665 (2014) - Valls, Alba; Grivé, Mireia; Riba, Olga; Morales, Maita; Spahiu, Kastriot
ABSTRACT: In the KBS-3 repository concept and safety analysis, the copper container with a cast iron insert plays a central role in assuring isolation of the waste from the surrounding during long periods of time. All processes that affect its stability are thoroughly analysed, including potential detrimental processes inside the canister. For this reason, an estimation of the helium produced during the long term decay of alpha emitters in the spent fuel is necessary to evaluate if the pressures generated inside can have consequences for the canister. The spent nuclear fuel to be disposed of in Sweden is mainly LWR fuel. The maximum burn-up expected is 60 MWd/kg U for BWR and PWR. A small quantity of BWR MOX is expected to be stored with a maximum burn-up of 50 MWd/kg U. This work has focused on carrying out calculations of the amounts of He generated during more than 1 million years in Swedish spent nuclear fuels with a benchmarking exercise by using both codes AMBER and Origen-ARP. The performance and agreement of the codes in the He generation from α-decay have been checked and validated against data reported in literature [1]. In the calculation of the maximal pressure inside the canister, the quantity of helium used to pre-pressurise the fuel rods has been accounted for. The pressure inside the canister due to He generation is at all times much lower than the hydrostatic pressure and/or the bentonite swelling pressure outside the canister.